1999
DOI: 10.1016/s0014-5793(99)00823-6
|View full text |Cite
|
Sign up to set email alerts
|

A family of structurally related RING finger proteins interacts specificallywith the ubiquitin‐conjugating enzyme UbcM41

Abstract: The ubiquitin-conjugating enzyme UbcM4 was previously shown to be necessary for normal mouse development. As a first step in identifying target proteins or proteins involved in the specificity of UbcM4-mediated ubiquitylation, we have isolated seven cDNAs encoding proteins that specifically interact with UbcM4 but with none of the other Ubcs tested. This interaction was observed in yeast as well as in mammalian cells. With one exception, all U__bcM4-interacting proteins (UIPs) belong to a family of proteins th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Before it was identified as a component of LUBAC, HOIL-1 was independently cloned and variously described as a binding partner and E3 ubiquitin ligase for oxidized iron regulatory protein 2 (IRP2) ( Yamanaka et al, 2003 ), a protein associated with hepatitis B virus X protein ( Cong et al, 1997 ), a binding partner of protein kinase C (PKC) ( Tokunaga et al, 1998 ), and a specific interactor with the ubiquitin conjugating enzyme UBE2L3 ( Martinez-Noel et al, 1999 ). Early work characterized HOIL-1 as a K48-specific ubiquitin ligase ( Yamanaka et al, 2003 ; Bayle et al, 2006 ; Zenke-Kawasaki et al, 2007 ; Zhang et al, 2008 ; Rana et al, 2013 ; Queisser et al, 2014 ) whereas an in vitro study from 2012 found HOIL-1 to possess an extremely weak E3 ligase activity that synthesized purely Met1-linked ubiquitin chains ( Stieglitz et al, 2012 ).…”
Section: Ubiquitin-oxyester Linkagesmentioning
confidence: 99%
“…Before it was identified as a component of LUBAC, HOIL-1 was independently cloned and variously described as a binding partner and E3 ubiquitin ligase for oxidized iron regulatory protein 2 (IRP2) ( Yamanaka et al, 2003 ), a protein associated with hepatitis B virus X protein ( Cong et al, 1997 ), a binding partner of protein kinase C (PKC) ( Tokunaga et al, 1998 ), and a specific interactor with the ubiquitin conjugating enzyme UBE2L3 ( Martinez-Noel et al, 1999 ). Early work characterized HOIL-1 as a K48-specific ubiquitin ligase ( Yamanaka et al, 2003 ; Bayle et al, 2006 ; Zenke-Kawasaki et al, 2007 ; Zhang et al, 2008 ; Rana et al, 2013 ; Queisser et al, 2014 ) whereas an in vitro study from 2012 found HOIL-1 to possess an extremely weak E3 ligase activity that synthesized purely Met1-linked ubiquitin chains ( Stieglitz et al, 2012 ).…”
Section: Ubiquitin-oxyester Linkagesmentioning
confidence: 99%
“…Protein-protein interaction studies first attracted attention to the RBR proteins. For example, XAP3 [23] and rat RBCK1 [11] were discovered with the regulatory domain of protein kinase C-β-interacting protein as a bait, and the Ariadne proteins were found as interaction partners of ubiquitin-conjugating enzymes (E2s) in fruit flies, mice and humans [24-27]. The putative Ariadne-like E3 ubiquitin ligase PAUL appeared in a complex extracted with the cytoplasmic domain of the muscle-specific kinase (MuSK) as bait [28].…”
Section: Localization and Functionmentioning
confidence: 99%